LENGTH-WEIGHT RELATIONSHIP OF THREE INDIGENOUS FRESHWATER FISH SPECIES FROM MAHARASHTRA, INDIA - GHATGE, SWAPNIL; SHETKAR, MAHESH; PATIL, KRISHNA; KHARATMOL, BALAJI (Journal of the Inland Fisheries Society of India, 2024)
The length–weight relationship (LWR) is a fundamental concept in fish biology, describing the quantitative relationship between two key morphological traits-length and weight-at both individual and population levels. It is a critical tool for assessing somatic growth, classified as isometric or allometric (Le Cren, 1951; Froese, 2006; Froese et al., 2011; Jana et al., 2024), and plays a central role in fisheries science. LWRs provide essential insights into condition factors, growth dynamics, and biomass estimations, all of which are vital for sustainable fisheries management and conservation efforts. Moreover, LWRs contribute to life history analyses (Petrakis and Stergiou, 1995), facilitate comparisons across sexes, seasons, and geographical regions (Moutopoulos et al., 2011, Mondal et al., 2023), and serve as indicators of environmental productivity and trophic status (Tsoumani et al., 2006; Moutopoulos et al., 2011). They also assist in differentiating stocks and conducting morphological assessments among species and populations (Moutopoulos and Stergiou, 2002; Santos et al., 2002; King, 2007; Bhakta et al., 2019). Despite their broad utility, LWR data remain unavailable for a majority of fish species globally only 14.3% of the world’s 33,500 species are represented in Fish Base (Froese and Pauly, 2024), underscoring the urgency for more region- and species-specific studies.